2018
DOI: 10.1111/acel.12778
|View full text |Cite
|
Sign up to set email alerts
|

Social stress shortens lifespan in mice

Abstract: SummaryStress and low socioeconomic status in humans confer increased vulnerability to morbidity and mortality. However, this association is not mechanistically understood nor has its causation been explored in animal models thus far. Recently, cellular senescence has been suggested as a potential mechanism linking lifelong stress to age‐related diseases and shorter life expectancy in humans. Here, we established a causal role for lifelong social stress on shortening lifespan and increasing the risk of cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 71 publications
4
95
0
1
Order By: Relevance
“…Both objective and perceived SES impact human health, mortality, morbidity, and susceptibility to psychiatric disorders such as depression or anxiety (Farah, 2017;Freeman et al, 2016;Hoebel et al, 2017;McEwen and Gianaros, 2010;Shaked et al, 2016;Wetherall et al, 2019). These outcomes resemble findings related to social dominance in mice (Bartolomucci, 2007;Pallé et al, 2019;Razzoli et al, 2018). Intriguingly, some human studies have identified sex differences in the relationship between SES and stress-related psychopathologies (Kosidou et al, 2011;Mwinyi et al, 2017;Peplinski et al, 2018).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Both objective and perceived SES impact human health, mortality, morbidity, and susceptibility to psychiatric disorders such as depression or anxiety (Farah, 2017;Freeman et al, 2016;Hoebel et al, 2017;McEwen and Gianaros, 2010;Shaked et al, 2016;Wetherall et al, 2019). These outcomes resemble findings related to social dominance in mice (Bartolomucci, 2007;Pallé et al, 2019;Razzoli et al, 2018). Intriguingly, some human studies have identified sex differences in the relationship between SES and stress-related psychopathologies (Kosidou et al, 2011;Mwinyi et al, 2017;Peplinski et al, 2018).…”
Section: Discussionmentioning
confidence: 85%
“…As a consequence, an individual's position in the dominance hierarchy has important consequences, including preferential access to food, shelter, and mates (Drews, 1993). Social rank within male hierarchies is also known to influence health, hormonal profile, brain function, metabolism and mortality (Pallé et al, 2019;Razzoli et al, 2018). For instance, subordinate individuals display increased anxiety-like behavior, a suppressed immune response, higher basal corticosterone levels, and reduced life span (Bartolomucci, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Among the known endogenous causes of this phenotype are DNA damage, dysfunctional telomeres, epigenomic disruption, mitogenic signals and oxidative stress 56 . The non-endogenous contributors are thought to include chronic infections 57 , lifestyle-induced obesity 58 , microbiome dysbiosis 59 , diet 60 , social and cultural changes 61,62 and environmental and industrial toxicants 63 . The fact that differences exist in the extent to which older adults exhibit SCI 52,64 is thought to be indicative of inter-individual differences in exposure to these and other related pro-inflammatory factors, although studies documenting within-person associations between these risk factors and SCI are limited.…”
Section: Sources Of Systemic Chronic Inflammationmentioning
confidence: 99%
“…In social organisms, the interactions resulting from regular contact with related and unrelated animals may have profound effects on individual physiology, health, and fitness (Sapolsky 1992;Bartolomucci 2007;Razzoli et al 2018). Studies have highlighted both positive and negative effects of social interactions (or lack thereof) on individual metabolic rate (Stefanski and Engler 1998;Sloman et al 2000; Willis and Brigham 2007;Cao and Dornhaus 2008), immunity (Stefanski and Engler 1998;de Groot et al 2001), and oxidative stress (Nation et al 2008;Zhao et al 2013;Beaulieu et al 2014;Lardy et al 2016), as well as gene regulation and cellular maintenance (Kotrschal et al 2007;Tung et al 2012;Aydinonat et al 2014).…”
Section: Introductionmentioning
confidence: 99%